JISIoT 2022
DOI: 10.54216/jisiot.070204
|View full text |Cite
|
Sign up to set email alerts
|

An effective model for Selection of the best IoT platform: A critical review of challenges and solutions

Abstract: The process of making an informed decision on which Internet of Things (IoT) platform to choose is an extremely important one in the modern world. The choice procedure is made more difficult as a result of (a) the vast number of IoT platforms that are offered on the market for IoT applications and (b) the wide diversity of functions and solutions that are provided by these platforms. In this article, the multi-criteria decision-making (MCDM) methodologies for selecting the specific Internet of Things platform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A comparison of SAW, TOPSIS, VIKOR, and COPRAS is presented in Table 3 [65][66][67][68][69]. [34], selection of IoT applications [44] Selection of IoT sensors [34,41], selection of IoT service [35,40,43], selection of IoT platform [51,52] Selection of IoT sensors [34], selecting an IoT platform in Supply Chain networks [5] Selection of IoT devices [47] Comparisons between the methods [65,68,69] [65-67,69] [65-67] [ [65][66][67][68] In [65], a comparison was made between the SAW, TOPSIS, ELECTRE, VIKOR, and COPRAS methods, considered separately, in the field of energy technology selection. It was found that changes in the weights had the greatest impact on the performance of the options.…”
Section: Choosing Multi-criteria Methods For Solving Selection Proble...mentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of SAW, TOPSIS, VIKOR, and COPRAS is presented in Table 3 [65][66][67][68][69]. [34], selection of IoT applications [44] Selection of IoT sensors [34,41], selection of IoT service [35,40,43], selection of IoT platform [51,52] Selection of IoT sensors [34], selecting an IoT platform in Supply Chain networks [5] Selection of IoT devices [47] Comparisons between the methods [65,68,69] [65-67,69] [65-67] [ [65][66][67][68] In [65], a comparison was made between the SAW, TOPSIS, ELECTRE, VIKOR, and COPRAS methods, considered separately, in the field of energy technology selection. It was found that changes in the weights had the greatest impact on the performance of the options.…”
Section: Choosing Multi-criteria Methods For Solving Selection Proble...mentioning
confidence: 99%
“…The DMs select a set of criteria (based on experience and literature reviews [4,37,42,48,49,51,52,59]). These criteria are of two categories: IoT platform requirements and criteria for IoT platform vendors.…”
Section: Application Of the Hybrid Group Multi-criteria Approach For ...mentioning
confidence: 99%